Simultaneous detection of electronic structure changes from two elements of a bifunctional catalyst using wavelength-dispersive X-ray emission spectroscopy and in situ electrochemistry. Issue 14 (6th March 2015) - Gul, Sheraz; Ng, Jia Wei Desmond; Alonso-Mori, Roberto; Kern, Jan; Sokaras, Dimosthenis; Anzenberg, Eitan; Lassalle-Kaiser, Benedikt; Gorlin, Yelena; Weng, Tsu-Chien; Zwart, Petrus H.; Zhang, Jin Z.; Bergmann, Uwe; et al.
Abstract : A method of simultaneously probing the electronic structure of multiple metal centers using wavelength-dispersive X-ray emission spectroscopy was developed. Abstract : Multielectron catalytic reactions, such as water oxidation, nitrogen reduction, or hydrogen production in enzymes and inorganic catalysts often involve multimetallic clusters. In these systems, the reaction takes place between metals or metals and ligands to facilitate charge transfer, bond formation/breaking, substrate binding, and release of products. In this study, we present a method to detect X-ray emission signals from multiple elements simultaneously, which allows for the study of charge transfer and the sequential chemistry occurring between elements. Kβ X-ray emission spectroscopy (XES) probes charge and spin states of metals as well as their ligand environment. A wavelength-dispersive spectrometer based on the von Hamos geometry was used to disperse Kβ signals of multiple elements onto a position detector, enabling an XES spectrum to be measured in a single-shot mode. This overcomes the scanning needs of the scanning spectrometers, providing data free from temporal and normalization errors and therefore ideal to follow sequential chemistry at multiple sites. We have applied this method to study MnO x -based bifunctional electrocatalysts for the oxygen evolution reaction (OER) and the oxygen reduction reaction (ORR). In particular, we investigated the effects of adding a secondary element, Ni, to form MnNiO x and its impact on the chemical states and catalytic activity, by tracking the redox characteristics of each element upon sweeping the electrode potential. The detection scheme we describe here is general and can be applied to time-resolved studies of materials consisting of multiple elements, to follow the dynamics of catalytic and electron transfer reactions.